The Influence of Core Self-Evaluation and Cyberloafing Behavior on Innovative Work Behavior Among Employees in the Creative Industry in Indonesia - Adinda Nabela Putri; Habibullah Jimad; Nova Mardiana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The creative industry in Indonesia has a significant contribution to the country's economy, so innovative work behavior is needed to be able to maintain and build the creative industry in order to adapt to changes or developments in its competitors. Many factors influence innovative work behavior, including core self-evaluation and cyberloafing behavior. This study aims to examine the effect of core self-evaluation and cyberloafing behavior on innovative work behavior. Data were collected using a questionnaire and obtained 165 employees of publishing companies and animation studios in Indonesia as respondents. The data that has been collected will be analyzed using multiple linear regression analysis tools with the help of the SPSS 30 application. The results of this study support the proposed hypothesis, namely that core self-evaluation and cyberloafing behavior have a positive and significant effect on innovative work behavior. The researcher's suggestion is that companies are expected to try to reduce employee stress levels and increase employee motivation. In addition, companies are required to manage the use of instant messaging applications properly so as not to interfere with productivity and employees are expected to increase self-control so that cyberloafing is still within reasonable limits and does not harm the company. Finally, provide support and training and innovation development or conduct brainstorming sessions to encourage employees to create and implement new innovations.